Variation in phytoliths morphology of Erianthus arundinaceus - Chellappa, Jayabose; Bhaskaran, A; Palaniswami, C (Journal of Sugarcane Research, 2021)
Five improved Erianthus arundinaceus clones were studied for variations in phytoliths present in leaves. Phytoliths were extracted by acid digestion and the morphology was studied by light microscopy. Phytoliths belonging to three classes viz., Eupanicoid, Festucoid and Chloridoid were identified in the samples. Variations in type and shape were observed among the clones studied. The results indicate that phytolith characteristics may be an important and reliable trait for clonal characterization in improved Erianthus clones and also there is a possibility of using this trait as a tool for the identification of species, hybrids and their parentage in sugarcane and their related genera.